Sleep Duration and Health Care Expenditures in the United States - Jasani, Foram (Med Care, 2020)
OBJECTIVE: To estimate the average incremental health care expenditures associated with habitual long and short duration of sleep as compared to healthy/average sleep duration. DATA SOURCE: Medical Expenditure Panel Survey (MEPS) data (2012; N=6,476) linked to the 2010–2011 National Health Interview Survey (NHIS). STUDY DESIGN: Annual differences in health care expenditures are estimated for habitual long and short duration sleepers as compared to average duration sleepers using two-part logit generalized linear regression models. PRINCIPAL FINDINGS: Habitual short duration sleepers reported an additional $1,400 in total unadjusted health care expenditures compared to people with average sleep duration (p<0.01). After adjusting for demographics, socioeconomic factors, and health behavior factors, this difference remained significant with an additional $1,278 in total healthcare expenditures over average duration sleepers (p<0.05). Long duration sleepers reported even higher, $2,994 additional health care expenditures over average duration sleepers. This difference in health care expenditures remained significantly high ($1,500, p<0.01) in the adjusted model. Expenditure differences are more pronounced for inpatient hospitalization, office expenses, prescription expenses and home health care expenditures. CONCLUSION: Habitual short and long sleep duration is associated with higher health care expenditures, which is consistent with the association between unhealthy sleep duration and poorer health outcomes.